Complexos de cobre(II) e oxovanádio(IV) com bases de Schiff Quirais: preparação, caracterização e alguns ensaios catalíticos - Romera, Sandra (2007)
Salen complexes are an important class of coordination compounds, which have been used to catalyze a wide variety of reactions. The salen complexes have emerged as efficient and practical catalysts for the asymmetric oxidation of various organic substrates. In this thesis, copper(II) and oxovanadium(IV) complexes of the salcn type ligand [salcn= N, N -bis- (salicylidene)-1,2-cyclohexanediamine] have been investigated as catalysts for oxidation of organic sulfide. The first part of this work describes the synthesis and characterization of the free ligands and copper(II) and oxovanadium(IV) complexes. The combination of four complementary techniques (IR, UV-vis, 1HNMR-13CNMR and X-ray) made possible the characterization of the free ligands and complexes. Six unpublished crystallographic structures were determined: four ligands and two oxovanadium(IV) complexes . In the second part of this research were studied catalytic properties of some complexes in oxidation of phenyl methyl sulfide using acetonitrile as the solvent and hydrogen peroxide and t-butylperoxide as the oxidant. The [Cu(salcn)] and [VO(salcn)] with electrons donors and electrons withdrawing substituents were tested for catalytic oxidation. The effect of reaction conditions on activity with various oxidants gave distinctly different yields. The complex trans-(±)-[Cu(5- Clsalcn) showed the best result, with 73% of the sulfide conversion. This is result was showed with hydrogen peroxide as the oxidant. The yields obtained for the other compounds vary of 11-32%.